2015
DOI: 10.1210/jc.2014-4449
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin K and the Metabolic Syndrome: A 10-Year Follow-Up Study in Adults

Abstract: This study shows that a high intake of menaquinones and high vitamin K status are associated with a lower occurrence of MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 36 publications
1
52
0
1
Order By: Relevance
“…Our data confirmed high plasma dp-ucMGP levels in advanced non-dialysis CKD patients when compared with the levels measured in healthy subjects [20,21], whereas they were lower than those in previously reported in HD populations [16,22,23]. In the present study we showed a strong inverse association between kidney function assessed by eGFR and plasma dp-ucMGP concentrations in non-dialysis patients with CKD stage 4-5.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data confirmed high plasma dp-ucMGP levels in advanced non-dialysis CKD patients when compared with the levels measured in healthy subjects [20,21], whereas they were lower than those in previously reported in HD populations [16,22,23]. In the present study we showed a strong inverse association between kidney function assessed by eGFR and plasma dp-ucMGP concentrations in non-dialysis patients with CKD stage 4-5.…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, Dalmeijer et al did not observe any changes in lipid profile during vitamin K2 supplementation among healthy men and postmenopausal women [20]. Dam et al recently reported that high intake of menaquinone was associated with lower incidence of metabolic syndrome and showed an association between triglycerides and dp-ucMGP concentrations [21].…”
Section: Discussionmentioning
confidence: 96%
“…Hypotensive drugs were also used. [36] . Dutch older adults (aged 40-80 years, 400 men, 402 women) were followed for 8.14 years.…”
Section: Involvement Of Vitamin K 2 -Dependent Pathways In Dmmentioning
confidence: 99%
“…17 ). Matrix Gla protein is also γ-carboxylated through a vitamin K 2 -dependent processes, and the plasma level of uc-matrix Gla protein was positively associated with MetS [36] . In older adults, elevated levels of c-Ocn and total Ocn, but not of uc-Ocn, were associated with lower insulin resistance [37] ( fig.…”
Section: Involvement Of Vitamin K 2 -Dependent Pathways In Dmmentioning
confidence: 99%
“…Several studies have tried to shed light on the dietary determinant of MetS. 5, 6, 7, 8, 9, 10, 11, 12 Some of their limitations include relatively small sample size of the studies, 5, 7, 8, 10 lack of diversity of the populations, 12 limitation in generalizability of the findings 12 and single-nutrient approach, 6, 7, 8, 9, 10, 11 whereas diet by definition is complex. As a result of more recognition of limitations inherent to the single-nutrient approach, dietary pattern analysis has emerged as an attractive alternative approach for examining the effect of overall diet reflecting the real-world eating behaviors of the population.…”
Section: Introductionmentioning
confidence: 99%